First person - Craig Keenan (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Craig Keenan is first author on 'Post-traumatic osteoarthritis development is not modified by postnatal chondrocyte deletion of Ccn2', published in DMM. Craig conducted the research described in this article while a postdoctoral research associate in Dr Blandine Poulet's lab at the University of Liverpool, Liverpool, UK. He is now a lecturer in vertebrate physiology in the lab of Dr Jason Kirby at Liverpool John Moores University, Liverpool, UK, investigating the roles of cartilage and bone in the pathogenesis of degenerative joint disease.